2022
DOI: 10.1101/2022.04.24.489283
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular and functional characterization of theDrosophila melanogasterconserved smORFome

Abstract: SummaryShort polypeptides encoded by small open reading frames (smORFs) are ubiquitously found in eukaryotic genomes and are important regulators of physiology, development, and mitochondrial processes. Here, we focus on a subset of 194 smORFs that are evolutionarily conserved between Drosophila melanogaster and humans. Many of these smORFs are conserved broadly in the bilaterian lineage, with ∼60 conserved in plants. Within these conserved smORFs, we observed remarkably heterogenous spatial and temporal expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Here, through an effort to systematically characterize human-conserved smORF genes in Drosophila ( Bosch et al, 2022 ), we identified two previously unstudied smORF peptides CG32736-PB and CG42308-PA that we named Sloth1 and Sloth2 based on their mutant phenotypes. Remarkably, both peptides are translated from the same transcript and share amino acid sequence similarity, suggesting that they encode paralogs.…”
Section: Introductionmentioning
confidence: 99%
“…Here, through an effort to systematically characterize human-conserved smORF genes in Drosophila ( Bosch et al, 2022 ), we identified two previously unstudied smORF peptides CG32736-PB and CG42308-PA that we named Sloth1 and Sloth2 based on their mutant phenotypes. Remarkably, both peptides are translated from the same transcript and share amino acid sequence similarity, suggesting that they encode paralogs.…”
Section: Introductionmentioning
confidence: 99%